(untitled) (International Journal of Food and Nutritional Sciences, 2019)
The emergence of 5G and subsequent generations of networks is expected to offer a wide range of services with diverse specifications. Notably, network slicing has been identified as a key innovation in enabling the provision of many services within 5G networks. By embracing network slicing, a transition is made from a networking-as-an-infrastructure model to a networking-as-a-service model, making it possible to support a multitude of 5G smart services with varying specifications. Despite the extensive coverage of network slicing in assessments and instructional videos, there remains a need for a comprehensive exploration of its taxonomic structure and prerequisites. In this article, we provide a detailed analysis of the most significant advancements in network slicing and how they have facilitated the emergence of numerous intelligent applications in the realm of the Internet of Things (IoT). We establish a taxonomy for network slicing based on the following criteria: fundamental design principles, enablers, objectives for slicing resources, plans for network functionality chaining, physical infrastructure, and security considerations. Additionally, we delve into the essential requirements for implementing innovative services through network slicing. Lastly, we shed light on ongoing research efforts and potential standards related to network slicing.